Endovascular repair of the ascending aorta: the last frontier? - Kotelis, Drosos; Kalder, Johannes; Jacobs, Michael J. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Starting at the infrarenal portion of the aorta, endovascular aortic repair with stent-grafts has evolved to the therapy of first choice for a variety of aortic pathologies and the majority of patients (1-3). The endovascular revolution has been galloping within two decades from the infrarenal aorta towards the thoracic and thoracoabdominal aorta, and has reached the aortic arch, with branched devices now enabling total endovascular solutions (4,5). The ascending aorta is anatomically the last frontier of the evolution of endovascular aortic therapies.